Literature and Honour - Aasta Marie Bjorvand Bjørkøy (Scandinavian University Press (Universitetsforlaget), 2017)
What is honour, and how does it affect our lives? In contemporary Western cultures, honour seems to have lost its dominant role as a key concept for denoting central dynamics of human life, both individually and socially. In the Scandinavian countries, a slow revolution has taken place throughout history from the strong Norse honour culture to the post-war egalitarian and equality-oriented welfare society which appears to be an after-honour culture. What are the reasons for this weakening, and what are its consequences? Are we living with new forms of honour, and what does it mean to live in an after-honour culture? The focal point and chief target of the discussions is literature, primarily Scandinavian, but also other textual expressions. The book is aimed at readers interested in literature, but the topic is interdisciplinary and should therefore appeal to a wider audience. This volume emanates from the project After Honour, initiated by the research group Literature and Affect at Institute of Scandinavian Studies, University of Oslo. The 15 articles are written by scholars from Norway, Denmark and Iceland: Per Thomas Andersen, Aasta Marie Bjorvand Bjørkøy, Mads B. Claudi, Johanne Walle Jomisko de Figueiredo, Jon Gunnar Jørgensen, Anne-Marie Mai, Thorstein Norheim, Nasim Karim, Jan Erik Rekdal, Peter Simonsen, Simen Syvertsen, Cecilie Takle, Torfi H. Tulinius and Mikkel Bruun Zangenberg.